Reconstructing the ancestor of Mycobacterium leprae: The dynamics of gene loss and genome reduction - Gómez-Valero, Laura; Rocha, Eduardo P.C.; Latorre, Amparo; Silva, Francisco J.

(untitled) (Genome Research, 2007)
We have reconstructed the gene content and order of the last common ancestor of the human pathogens Mycobacterium leprae and Mycobacterium tuberculosis. During the reductive evolution of M. leprae, 1537 of 2977 ancestral genes were lost, among which we found 177 previously unnoticed pseudogenes. We find evidence that a massive gene inactivation took place very recently in the M. leprae lineage, leading to the loss of hundreds of ancestral genes. A large proportion of their nucleotide content (∼89%) still remains in the genome, which allowed us to characterize and date them. The age of the pseudogenes was computed using a new methodology based on the rates and patterns of substitution in the pseudogenes and functional orthologous genes of closely related genomes. The position of the genes that were lost in the ancestor’s genome revealed that the process of function loss and degradation mainly took place through a gene-to-gene inactivation process, followed by the gradual loss of their DNA. This suggests a scenario of massive genome reduction through many nearly simultaneous pseudogenization events, leading to a highly specialized pathogen.